The effectiveness of Present Malaysia Productions Sdn. Bhd in determining the successful of event planning management / Suhaida Mazlan - Mazlan, Suhaida (2008)
Event planning management in Malaysia is considering as infant industries in the country. However, planning and its process play as a key role in the company and the management of special or big event such as Present Malaysian Productions Sdn. Bhd. which organized the world marching band competition. It is because the larger and more complex events become the more detailed and systematic the planning will have to be. The study identified the factors that can influence the planning management in Malaysia that practiced by Present Malaysian Productions Sdn. Bhd. during KLWMBC 2008 event recently. According to the findings, the event which organized by the company is proven that planning management is important in order to guaranteed the event would be successful. The study also indicates that a lot of things need to be improved to ensure in organizing a better event in the future with a better planning management and the need to identify the objectives and goals, before organizing an event.